Physical and Flavor Quality of Some Potential Varieties of Arabica Coffee in Several Interval Storage Periods - Yusianto .; Retno Hulupi; Sulistyowati .; Surip Mawardi; Cahya Ismayadi (Indonesian Coffee and Cocoa Research Institute, 2007)
Coffee storage was an active process, where the quality and flavor was depend on the origin, humidity, temperature, period, and ware house condition. The objective of this research was to know quality and flavor of some Arabica coffee varieties in interval of storage periods. The examined coffee varieties were BP 416 A, BP 430 A, BP 432 A, BP 509 A, BP 542 A, P 88, AS 1, S 795, and USDA-762. The treatments were recent harvest, one and two years stored green coffee. The green coffee were wet processed, sun dried, packed in polyethylene bags, one kg/pack and placed in some covered plastic boxes. The boxes were stored in ware house covered with wavy asbes roof and flat asbes ceiling. The green coffee was examined for its moisture content, color, and bulk density. The green coffee was roasted at medium level, and then examined for its the bulk density, yield, volume of swelling, and color of the roasted and powdered. The flavors examination was blind test method. The research showed that storage period significantly influenced the moisture content, color, and bulk density of green coffee, yield, volume of swelling, color of roasted coffee, color, and flavor profile of coffee powder. Those varieties tested showed significantly different on the moisture content, green coffee color, roasted coffee color, coffee powder color, and the profile flavor. The storage period influenced the green coffee color from greenish-gray to yellowish-red. The bulk density of green coffee decreased. The varieties that showed a little color changeduring storage, were BP 430 A,BP 416 A, AS 1, and S 795. One year of storage periode, the green coffee was still had the original color, but after two years, the original color had changed totally. The powder of recent harvest coffee was darker than that of one and two years storage. One year stored coffee had higher quality of aroma, intensity of aroma, quality of flavor, intensity of flavor, acidity, quality of after taste, intensity of after taste and preference, than the recent harvest and two years stored coffee. recent harvest had higher body, bitterness, and astringency, than that of one and two years stored coffee. The main off-flavor of recent harvest coffee was green and grassy, the one year stored coffee was harsh, woody, earthy, and sour, while the two years stored coffee was harsh, woody, earthy and moldy. The flavor change in the first year was higher than in the second year storage. The varieties, that had lowest change on flavor during storage, were BP 416 A, AS 1, P 88, BP 432 A and S 795. Key words: Coffee, Arabica, variety, clone, storage, quality, flavor, color.